Nitrogen Oxides and Ozone in the Tropopause Region of the Northern Hemisphere: Measurements from Commercial Aircraft in 1995/96 and 1997 - Brunner, D.; Staehelin, J.; Jeker, D.; Wernli, W.; Schumann, U. (2001)
Measurements of nitrogen oxides (NO and NO2) and ozone (O3) were performed from a Swissair B-747 passenger aircraft in two extended time periods (May 1995 to May 1996, August to November 1997) in the framework of the Swiss NOXAR and the European POLINAT 2 project. The measurements were obtained on a total of 623 flights between Europe and destinations in the United States and the Far East. NO2 measurements were obtained only after December 1995 and were less precise than the NO measurements. Therefore daytime NO2 values were derived from measured NO and O3 concentrations assuming photostationary equilibrium. The completed NOx data set (measured NO, measured NO2 during night, and calculated NO2 during day) includes a complete annual cycle and is the most extensive and representative data set currently available for the upper troposphere (UT) and the lower stratosphere (LS) covering a significant proportion of the northern hemisphere between 15°N and 65°N. NOx concentrations in midlatitudes (30°−60°N) showed a marked seasonal variation both in the UT and the LS with a maximum in summer (median/mean values of 159/264 pptv in UT, 199/237 pptv in LS) and a minimum in winter (51/99 pptv in UT, 67/91 pptv in LS). Mean NOx concentrations were generally much higher than the respective median values, in particular in the UT, which reflects the important contribution from comparatively few very high concentrations observed in large-scale convection/lightning and small-scale aircraft plumes. Seasonal mean NOx concentrations in the UT were up to 3–4 times higher over continental regions than over the North Atlantic during summer. Lightning production of NO and convective vertical transport from the polluted boundary layer thus appear to have dominated the upper tropospheric NOx budget over these continental regions, particularly during summer. Ozone concentrations at aircraft cruising levels typically varied by an order of magnitude due to the strong vertical gradient in the LS. Seasonal mean values were dominated by ...